Roadmap for the implementation of an enterprise architecture framework oriented to institutions of higher education in Ecuador - Abad Espinoza, M. (2010)
This paper proposes a comprehensive and integrated roadmap for the implementation of an enterprise architecture framework in the higher education institutions of Ecuador with the purpose to get the best utilization of the resources of IT (to improve the quality of the services, to rationalize the technical administration and to finance the assets of IT, and to improve the management of the resources and project portfolios), through identifying the appropriate current and emerging best practices, methodologies (EA frameworks), and tools for each of the major enterprise architecture components that must be addressed in any approach. © 2010 IEEE.